Chronic stability of local field potentials from standard and modified Blackrock microelectrode arrays implanted in the rat motor cortex. (18th October 2019) - Usoro, Joshua O; Shih, Ellen; Black, Bryan J; Rihani, Rashed T; Abbott, Justin; Chakraborty, Bitan; Pancrazio, Joseph J; Cogan, Stuart F
Abstract: Utah electrode arrays (UEAs) enable the recording of neuronal activity that informs the understanding of cortical connectivity and function, and can be used to control brain-machine/computer interfaces. However, UEAs have shown a reduced ability to resolve single unit activity (SUA) over time, prompting efforts such as the use of alternative insulation materials and reliance of local field potentials (LFPs) to improve device robustness and stability of neuroprosthetic control signals, respectively. The effect of different electrode insulation materials on LFP stability, particularly with UEAs, has not been extensively investigated, especially in rats, which provide a well-studied model for behavior and motor cortex injury. Here, we report the chronic stability of LFPs from both Parylene-C- and amorphous silicon carbide-encapsulated UEAs implanted in the rat motor cortex. We observed a decrease in bandpower in anesthetized rats for both array types that converged to the same magnitude at 30 weeks. In awake, freely-behaving rats however, there was relatively stable bandpower in both array types across individual frequency bands. In total, our results are consistent with studies performed in non-human primates, suggesting that chronic LFP stability trends are similar across both animal models.